2021
DOI: 10.4269/ajtmh.21-0509
|View full text |Cite
|
Sign up to set email alerts
|

Post-Discharge Symptoms among Hospitalized COVID-19 Patients in Nigeria: A Single-Center Study

Abstract: There is a paucity of studies on post-acute COVID-19 syndrome (PCS) among hospitalized COVID-19 survivors from Nigeria. We describe the frequency, types, and duration of post-discharge symptoms suggestive of PCS among previously hospitalized COVID-19 patients in a treatment center in Nigeria. We conducted a retrospective review of admission and post-discharge follow-up medical records of COVID-19 survivors admitted between April and December 2020. A standardized checklist was used to document post-discharge sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Approximately 21% of COVID‐19 hospitalised patients require care in an intensive care unit (ICU) (Centers for Disease Control and Prevention [CDC], 2022 ) for respiratory and/or cardiovascular complications. Following a COVID‐19 ICU hospitalisation, patients often experience common symptoms such as ongoing cough, shortness of breath, generalised weakness, fatigue, chest pain, memory deficits, confusion, and psychological distress that may take weeks to years to recover from—if at all (Halpin et al, 2020 ; Ogoina et al, 2021 ; Parotto et al, 2021 ). Further, patients who have been discharged from the ICU with health conditions similar to COVID‐19, such as acute respiratory distress syndrome, often require the support of family members to assist in disability management, recovery encouragement, and identification of formal support services (Hauschildt et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 21% of COVID‐19 hospitalised patients require care in an intensive care unit (ICU) (Centers for Disease Control and Prevention [CDC], 2022 ) for respiratory and/or cardiovascular complications. Following a COVID‐19 ICU hospitalisation, patients often experience common symptoms such as ongoing cough, shortness of breath, generalised weakness, fatigue, chest pain, memory deficits, confusion, and psychological distress that may take weeks to years to recover from—if at all (Halpin et al, 2020 ; Ogoina et al, 2021 ; Parotto et al, 2021 ). Further, patients who have been discharged from the ICU with health conditions similar to COVID‐19, such as acute respiratory distress syndrome, often require the support of family members to assist in disability management, recovery encouragement, and identification of formal support services (Hauschildt et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over a 7 to 238-day follow-up period, about three symptoms were reported per patient, and the development of post-acute COVID-19 syndrome was linked substantially with initial COVID-19 severity. The most prevalent symptoms reported by this cohort were cough, tiredness, and dyspnea [ 24 ]. Another study found that most COVID-19 patients who required hospitalization still have persisting symptoms even 110 days after release, particularly fatigue and dyspnea, underlining the necessity for long-term follow-up and rehabilitation programs for those patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of T2DM among patients with post-COVID-19 syndrome was estimated at 15% according to a recent meta-analysis (195), which was higher than the prevalence of DM in the general population (36). In three other studies, however, patients with DM were not more symptomatic than patients without DM during post-COVID-19 period (199)(200)(201).…”
Section: Post-discharge Implicationsmentioning
confidence: 98%